SAT0078 MAJOR CHANGES IN THERAPY PRODUCE SIGNIFICANT CLINICAL IMPROVEMENT ACROSS A BROAD RANGE OF CLINICAL DISEASE ACTIVITY IN US VETERANS WITH RHEUMATOID ARTHRITIS. (June 2019) - Cannon, Grant; Chen, Wei; Shen, Jincheng; Accortt, Neil; Collier, David; Sauer, Brian
Abstract : Background: Our recent work showed that 41% of patients with moderate/severe rheumatoid arthritis (RA) by Disease Activity Score for 28 joint count (DAS28) did not have changes in RA therapy as recommended by current guidelines (1). Reasons identified for the decision not to escalate therapy was provider's opinion that RA disease was adequately controlled despite moderate/severe disease activity by DAS28, and that changes in therapy may not produce significant improvements in disease activity (1). Objectives: 1) Compare short-term differences in ACR20 response between patients with and without a major therapeutic change (MTC) over a range of disease activity; 2) Determine whether ACR20 responses vary by disease activity measures (DAMs) used to assess disease activity (i.e., DAS28, Clinical Disease Activity Index [CDAI], Routine Assessment of Patient Index Data 3 [RAPID3]). Methods: Each clinic visit for US Veterans enrolled in the VA Rheumatoid Arthritis (VARA) registry was evaluated if the visit had: 1) a complete set of DAMs (DAS28, CDAI, RAPID3) recorded; 2) two other visits with all DAMs during the preceding 18 months separated by at least 60 days and one visit with all DAMs between 60 and 180 days following the visit date; 3) clinical data available for 18 months prior to visit date; and 4) ≥6 tender and ≥6 swollen joints at visit date. Each patient was assessed for MTC within 1 week before and 30 days after visit date. MTC was defined as any of the following: 1) initiation of new biologic or nonbiologic disease-modifying antirheumatic drug (DMARD) or prednisone (as new agent or after 90-day gap during baseline); 2) escalation of DMARD dose by ≥25%; or 3) increase in monthly average prednisone dose by 25%; and/or 4) injection of 2 or more joints with corticosteroids. Clinical improvement was defined as an ACR20 response comparing each eligible visit DAM to the first follow-up visit DAM observed between 60 and 180 days of the eligible visit date. ACR20 response was compared between eligible visits with and without a MTC and stratified by quartiles of disease activity by each DAM. The Generalized Estimating Equations (GEE) model was fitted using the exchangeable working covariance structure to account for clustering of visits within patients. Models for each DAM were adjusted for age, disease duration, race, seropositive status, comorbidities, disease stability, and recent medication changes in the observations period prior to the visit date. Results: There were 383 patients (92% were male, mean age was 62.9 years, mean disease duration was 12.5 years, 83% tested positive for rheumatoid factor, and 79% positive for anti-cyclic citrullinated peptide antibodies) who contributed 1, 193 eligible visits. Visits with a MTC had a higher rate of ACR20 response in comparison to visits without a MTC at all levels of disease activity. A MTC at a visit with the highest disease activity (quartile 4) consistently had the largest proportion of follow-up visits with an ACR20 response. The overall effect for MTC was statistically significant across all 3 DAMs. Across quartiles, the MTC group consistently had a higher proportion of follow-up visits with ACR20 response compared to the group without a MTC. Risk Ratios from the adjusted analysis are presented in the table. Conclusion: All patients with active RA have a significant potential to benefit with a MTC. This potential for improvement was seen across all degrees of disease activity and with all three DAMs. Reference: [1] Stever, et al. Utility of administrative and clinical data to predict major change in medical treatment in US Veterans enrolled in the Veterans Affairs Rheumatoid Arthritis (VARA) registry. Clin Exp Rheumatol; 2018Epub ahead of print. Disclosure of Interests: Grant Cannon Grant/research support from: Amgen Inc., Wei Chen Grant/research support from: Amgen Inc., Jincheng Shen: None declared, Neil Accortt Shareholder of: Amgen Inc., Employee of: Amgen Inc., David Collier Shareholder of: Amgen Inc., Employee of: Amgen Inc., Brian Sauer Grant/research support from: Amgen Inc.